Artes plásticas y relaciones lógico matemáticas en los niños de preparatoria de la Unidad Educativa Fiscomisional San Juan Bautista del Cantón Catamayo, periodo 2023 - 2024 - Salinas Aguilar, Ana Gabriela (2024)
Logical-mathematical relationships are a set of mechanisms that allow the interpretation and understanding of the world, leading to reasoning abilities enabling reflection on any topic of interest. This curriculum integration work aims to determine how the visual arts strengthen the logical-mathematical relationships among children at San Juan Bautista Fiscomisional School in Catamayo Canton, during the school year 2023-2024. The research design was quasi-experimental, with a mixed-method approach and a descriptive scope. Inductive, deductive, and analytical-synthetic methods were utilized. For the study, the Early Mathematical Evaluation Test (EMET) instrument was used, which revealed that 88% of the population was classified in the moderate, low, and very low levels, while 12% were in the high and very high levels. After the intervention, 40% of the children moved to the high level and 36% to the very high level. Therefore, it is concluded that the visual arts positively contributed, as an innovative and entertaining teaching method was evidenced through the manipulation of various materials, favoring the acquisition of fundamental mathematical knowledge and skills in children's learning. Keywords: Visual arts, skills, logical-mathematical, manipulation, high school.